2015
DOI: 10.1016/j.sbspro.2015.02.208
|View full text |Cite
|
Sign up to set email alerts
|

Considerations Related to the Efficiency of Sciences Lessons Based on IBSE Strategy

Abstract: Our study, conducted in relation to the concrete results of an investigative approach, aims to highlight the efficiency of Sciences lessons (Chemistry, Physics, Biology) designed in the PROFILES -Education through Science training program, lessons focused on instruction through scientific investigation (IBSE), a teaching strategy based on experimentation, questioning, discovery, problem solving, group work, likely to provide relevant learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The need for a more motivational school science that stimulates students' interest in science and science careers has been in fact iterated in many reports 6,7,8,9,10,11,12 . In recently published literature Sotáková et al 13 identified the effect of revising the thematic unit "Changes in Chemical Reactions" using IBSE method; Conceição et al 14 proposed a lesson study as a trigger for preservice physics and chemistry teachers; Fernandes et al 15 presented an analysis of inquiry-based science education and the possibility of employing Information and Communication Technology (ICT) as a supporting tool when performing inquiry activities in science teaching; a pragmatic use of motivational theory in science to enrich IBSE teaching practices was proposed by Andersen and Krogh 16 ; Checchetti 17 combined CLIL (Content and Language Integrated Learning) with IBSE (Inquiry Based Science Education) methodology to create a lesson on spectroscopy; Ellwood and Abrams 18 investigated how student social interactions within two approaches to an inquiry-based science curriculum could be related to student motivation and achievement outcomes; Tavares et al 19 considered advantages of science education outdoors through IBSE methodology; Dovigo and Rocco 20 evaluated European Inquiry-Based Education Projects through the Lens of Evaluation Capacity Building; Drăghicescu et al 21 highlighted the effectiveness of Science (Chemistry, Physics, Biology) lessons designed with IBSE approach; Trna 22 found which component of IBSE are suitable for gifted students in science and proposed a method to motivate science teachers to use science experiments 6 , Nurshamshida et al 23 examined how meaningful science learning could be achieved via the introduction of an inquiry-based Science approach in Chemistry teaching.…”
Section: Introductionmentioning
confidence: 99%
“…The need for a more motivational school science that stimulates students' interest in science and science careers has been in fact iterated in many reports 6,7,8,9,10,11,12 . In recently published literature Sotáková et al 13 identified the effect of revising the thematic unit "Changes in Chemical Reactions" using IBSE method; Conceição et al 14 proposed a lesson study as a trigger for preservice physics and chemistry teachers; Fernandes et al 15 presented an analysis of inquiry-based science education and the possibility of employing Information and Communication Technology (ICT) as a supporting tool when performing inquiry activities in science teaching; a pragmatic use of motivational theory in science to enrich IBSE teaching practices was proposed by Andersen and Krogh 16 ; Checchetti 17 combined CLIL (Content and Language Integrated Learning) with IBSE (Inquiry Based Science Education) methodology to create a lesson on spectroscopy; Ellwood and Abrams 18 investigated how student social interactions within two approaches to an inquiry-based science curriculum could be related to student motivation and achievement outcomes; Tavares et al 19 considered advantages of science education outdoors through IBSE methodology; Dovigo and Rocco 20 evaluated European Inquiry-Based Education Projects through the Lens of Evaluation Capacity Building; Drăghicescu et al 21 highlighted the effectiveness of Science (Chemistry, Physics, Biology) lessons designed with IBSE approach; Trna 22 found which component of IBSE are suitable for gifted students in science and proposed a method to motivate science teachers to use science experiments 6 , Nurshamshida et al 23 examined how meaningful science learning could be achieved via the introduction of an inquiry-based Science approach in Chemistry teaching.…”
Section: Introductionmentioning
confidence: 99%